Optical vortices in add-drop filters - B.P. Lapin; S.S. Aliyeva; M.A. Yavorsky; C.N. Alexeyev (Компьютерная оптика)
In this paper, we study the propagation of optical vortices (OVs) through an add-drop filter based on a multimode fiber. Using vector approximation and the transfer matrix formalism, we study the transmission of OVs through such a system. We obtain transmission curves for OVs and show that the add-drop filter can invert topological charges of incoming vortices. We suggest that such a system may be used for generating OV frequency combs. We also study a group delay time and argue that such a photonic-circuit element may be used in time delay lines for structured modes. In addition, we study orbital angular momentum transformation by such a system.